Development and validation of a high throughput LCâMS/MS method for simultaneous quantitation of pioglitazone and telmisartan in rat plasma andÂ itsÂ application to a pharmacokinetic study - Pinaki Sengupta; Bappaditya Chatterjee; Uttam Kumar Mandal; Bapi Gorain; Tapan Kumar Pal (Elsevier, 2017)
Management of cardiovascular risk factors in diabetes demands special attention due to their co-existence. Pioglitazone (PIO) and telmisartan (TLM) combination can be beneficial in effective control of cardiovascular complication in diabetes. In this research, weÂ developed and validated a high throughput LCâMS/MS method for simultaneous quantitation of PIO andÂ TLM in rat plasma. This developed method is more sensitive and can quantitate the analytes in relatively shorter period of time compared to the previously reported methods for their individual quantification. Moreover, till date, there is no bioanalytical method available to simultaneously quantitate PIO and TLM in a single run. The method was validated according to the USFDA guidelines for bioanalytical method validation. A linear response of the analytesÂ was observed over the range of 0.005â10Â Âµg/mL with satisfactory precision and accuracy. Accuracy at four quality control levels was within 94.27%â106.10%. TheÂ intra- and inter-day precision ranged from 2.32%â10.14 and 5.02%â8.12%, respectively. The method was reproducible and sensitive enough to quantitate PIO and TLM in rat plasma samples of a preclinical pharmacokinetic study. Due to the potentialÂ of PIO-TLM combination to be therapeutically explored, this method is expected to have significant usefulness in future. Keywords: LCâMS/MS, Rat plasma, Pharmacokinetic applicability, Telmisartan, Pioglitazone, Pharmacokinetic application